2010
DOI: 10.1007/s11632-010-0007-4
|View full text |Cite
|
Sign up to set email alerts
|

Maturity indices of Indian horse-chestnut (Aesculus indica Colebr.) seeds under temperate Kashmir conditions

Abstract: Our study on maturity indices of Aesculus indica Colebr. seeds was conducted under temperate Kashmir conditions in 2006. Seed collection was started from 15 July and continued until the maturation of seeds in December. The seeds were harvested fortnightly from identified trees and on each collection date maturity indices, viz. seed color, seed weight, moisture content, seed dimension, specific gravity and germination percentage were recorded. The study revealed that at the time of maturity (Nov.-Dec.) the seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Maturity of seeds also has been associated with seed moisture content, for example, Ricinus communis L. seed maturity was reported to occur at 22 % seed moisture content (Vallejos et al, 2011). Seeds of Aesculus indica Colebr, Albizzia lebbeck and Celtis australis had physiological maturity at 58, 52 and 32 % seed moisture content respectively (Majeed et al, 2010;Bhardwaj et al, 2002). Our research showed that seeds of H. Perotensis reached physiological maturity with fresh seed weight of 0.010 to 0.015 g, moisture content lower than 20 % and seed germination of 85 %.…”
Section: Discussionmentioning
confidence: 99%
“…Maturity of seeds also has been associated with seed moisture content, for example, Ricinus communis L. seed maturity was reported to occur at 22 % seed moisture content (Vallejos et al, 2011). Seeds of Aesculus indica Colebr, Albizzia lebbeck and Celtis australis had physiological maturity at 58, 52 and 32 % seed moisture content respectively (Majeed et al, 2010;Bhardwaj et al, 2002). Our research showed that seeds of H. Perotensis reached physiological maturity with fresh seed weight of 0.010 to 0.015 g, moisture content lower than 20 % and seed germination of 85 %.…”
Section: Discussionmentioning
confidence: 99%
“…5). A number of researchers (Sofi et al, 2016 in Acer caesium;Ahirwar, 2012 in Alangium lamarckii andMumtaz et al, 2009 in Aesculus indica) have correlated seed germination percent with maturity of seeds. At altitude A 1 germination per cent of 13.71 per cent was recorded at first collection in the first fortnight of August and subsequently increased to 67.37 percent at maturity.…”
Section: Fig 2 Altitudinal Variation In Specific Gravity At Different Stages Of Cones Maturity In Pinus Wallichianamentioning
confidence: 99%
“…Maturity of cones is ascertained by seed dispersal, which is the common indicator of seed maturity in conifers (Edwards, 1980). The mature seeds have higher vigour and potential for establishment of seedlings as compared to immature seeds (Sofi et al, 2016;Mumtaz et al, 2009). Fruit collection should only be started when seeds are sufficiently mature.…”
Section: Introductionmentioning
confidence: 99%
“…The tree is being widely used for afforestation and ornamental purposes as well as for fodder, wood as small timber, and branches for making charcoal. In the forests, Aesculus indica seeds are eaten by monkeys, bears and other wild animals as fodder (Majeed et al, 2009). The tree is commercially important and has high nutritional value as the fruits are fed to cattle and goats.…”
Section: Introductionmentioning
confidence: 99%